Assessment of cable forces at the London 2012 Olympic Stadium roof - Elsa de Sá Caetano (2013)
The London 2012 Olympic Stadium roof was constructed as a cable net covered by a flat PVC-coated polyester fabric membrane supported by an oval compression truss and an inner tension ring. As part of the geometric and mechanical control of the constructed structure, the forces installed in the most relevant cables were assessed using the vibration method. Particular characteristics of these cables, such as the flexibility of anchorages, the short length, low tension and bending effects were among the difficulties found, preventing the direct application of the vibrating chord formula to estimate force on the basis of measured natural frequencies. In order to reduce as much as possible the errors in force estimates, a methodology combining numerical finite element modeling with experimental testing was applied. This comprehended in particular the modeling of the cables with adjustable rotational springs, the corresponding constants being fitted on the basis of the measured natural frequencies. This paper describes the methodology applied in the identification of force in different conditions, showing that the combination of high-quality vibration measurements with finite element analysis of individual cables can provide a robust and powerful identification tool in many situations where the vibrating chord theory fails. Furthermore, the differences of pre-stress to theoretical values are characterised and discussed in face of the sensitivity of structural members to fabrication and erection tolerances.